Plant Nutrients for Citrus Trees - Mongi Zekri; Thomas A. Obreza (EDIS, 2003)
This document is SL 200, a fact sheet of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First printed: January 2003.